Volunteer Intention to Stay in Non-Governmental Organizations: Exploring the Role of Calling through the Lens of Work-as-Calling Theory to Strengthen the Economy - Handika, Cicih; Pusparini, Elok Savitri (International Journal of Economics Development Research (IJEDR), 2025)
This study examines the relationship between perceiving a calling and intention to stay among volunteers of non-governmental organisations (NGOs) in Jabodetabek, with the mediating role of living a calling. Through a quantitative approach and the Covariance-Based Structural Equation Modelling (CBSEM) method, data from 350 respondents were analyzed. The results showed that perceiving a calling has a significant influence on intention to stay, and living a calling strengthens the relationship. Managerial implications include the importance of programs that align with volunteers' intrinsic motivation, recognition of contributions, training, and the creation of a supportive work environment. This study is limited to the Jabodetabek area with a small sample size. Further studies are expected to cover a wider area and use mixed methods to enrich the results. This study provides practical insights for NGOs to improve volunteer retention through a calling-based approach.